Income distributions, inequality, and poverty in Asia, 1992 - 2010 - Duangkamon Chotikapanich; William E. Griffiths; D. S. Prasada Rao; Wasana Karunarathne (Asian Development Bank Institute (ADBI), 2014)
Income distributions for developing countries in Asia are modeled using beta-2 distributions, which are estimated by a method of moments procedure applied to grouped data. Estimated parameters of these distributions are used to calculate measures of inequality, poverty, and pro-poor growth in four time periods over 1992 - 2010. Changes in these measures are examined for 11 countries, with a major focus on the People's Republic of China (PRC), India, and Indonesia, which are separated into rural and urban regions. We find that the PRC has grown rapidly with increasing inequality accompanying this growth. India has been relatively stagnant. Indonesia has grown rapidly after suffering an initial set back from the Asian financial crisis in 1997.
Keywords: C13; C16; D31; 330; growth; inequality; poverty; income distribution